2015
DOI: 10.1016/j.schres.2015.07.050
|View full text |Cite
|
Sign up to set email alerts
|

Social defeat predicts paranoid appraisals in people at high risk for psychosis

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 68 publications
3
38
0
Order By: Relevance
“…Ordinal Logistic Regression (LOGIT) was used to explore baseline predictors (PEDQ and PQparanoia) of paranoid ideation in the VR environment. Based on the dataset, responses were grouped into four ordinal categories (corresponding to scores <10; 11-15; 16-25; >26) (Valmaggia et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Ordinal Logistic Regression (LOGIT) was used to explore baseline predictors (PEDQ and PQparanoia) of paranoid ideation in the VR environment. Based on the dataset, responses were grouped into four ordinal categories (corresponding to scores <10; 11-15; 16-25; >26) (Valmaggia et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…These experiences included traumatic events, social adversity, stressful life events, and subjective feelings of stress and inability to cope. [ 59 ] were associated with paranoid ideation in a VR social environment. The ability to use VR to study the effect of adverse life events on realtime response to social situations in a controlled environment offers an exiting new way to research what contributes to stress sensitivity.…”
Section: Discussionmentioning
confidence: 97%
“…Second, because the perception of social rank is closely tied to the social hierarchy and the assessment of individuals of being superior or inferior to others and, thus, more or less capable of competing for different biosocial goals. If these relatives perceive themselves as occupying an average/superior rank in their social hierarchy, they necessarily evaluate themselves as more capable to defend themselves, showing a decreased propensity to regard others as a potential source of damage or offence (e.g., Gilbert, 1998a;Lardinois et al, 2011;Valmaggia et al, 2015). Conversely, for patients with schizophrenia, if social comparison is key to interpersonal relationships, the more negative social comparison (not belonging or occupying a lower rank) may increase the probability of perceiving a social situation as threatening.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its important role on functional and adaptive social relationships, shame is also typically found in the onset and maintenance of a myriad of psychiatric problems and dysfunctional behaviours (Gilbert, 1998b;Johnson et al, 2014;Mills, 2008;Pinto-Gouveia, Matos, Castilho, & Xavier, 2014;Rizvi & Linehan, 2005), including paranoid beliefs, through self-depreciative thoughts and attributions of malevolence to others (Barreto Carvalho et al, 2015;Chadwick et al, 2005;Johnson et al, 2014;Trower & Chadwick, 1995). It is suggested that cognitive and emotional processing resulting from external shame triggers defensive responses of submissiveness aimed at appeasing and avoiding attacks of individuals who are regarded as powerful (more dominant, more attractive) and lead to the maintenance of more dysfunctional interpersonal processes (Gilbert, Davidson, Ekman, & Scherer, 1998;Lardinois et al, 2011;Valmaggia et al, 2015). Hence, social processes such as social comparison, subordination, and shame can also be key aspects in the aetiology and maintenance paranoid thoughts, it is psychological consequences and clinical implications to both clinical and nonclinical populations (Lataster, Collip, Lardinois, van Os, & Myin-Germeys, 2010;Valmaggia et al, 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation